1993
DOI: 10.1271/bbb.57.1811
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization ofβ-Fructofuranosidase fromAspergillus japonicusTIT-KJ1

Abstract: A beta-fructofuranosidase (EC 3.2.1.26) was purified to homogeneity from Aspergillus japonicus TIT-KJ1. The enzyme had an optimum pH for activity of 5.4 and pH stability at 7.0-8.4. The optimum temperature at pH 5.4 was 60 degrees C. The enzyme had a molecular weight of 236,000 with two subunits and an isoelectric point of pH 4.0. The enzyme was inactivated by 5 mM Hg2+ and Ag+. The enzyme had a high transfructosylating activity. Treatment of 50% (w/v) sucrose with the enzyme under optimum conditions afforded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 3 publications
2
27
0
Order By: Relevance
“…The pH activity curve agrees with the results of Duan et al (1993) as shown in Figure 1. There were some differences in activity of the enzymes at pH 8.5 where both the immobilized enzymes were more active than the free enzyme ( Figure 1).…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…The pH activity curve agrees with the results of Duan et al (1993) as shown in Figure 1. There were some differences in activity of the enzymes at pH 8.5 where both the immobilized enzymes were more active than the free enzyme ( Figure 1).…”
Section: Resultssupporting
confidence: 87%
“…After cultivation, the mycelium was harvested by filtration through a 250 mesh screen. The crude Ffase (b-fructofuranosidase) was extracted from the mycelium and was partially purified by preparative isoelectric focusing electrophoresis (IEF, Bio-Rad) following the procedures suggested by Duan et al (1993).…”
Section: Enzyme Production and Purificationmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously reported for the extracellular enzyme from A. phoenicis (Rustiguel et al, 2010), we found that 10 mM Ag þ increased the mycelial enzyme activity by 91%. Ag þ was reported to inhibit β-D-fructofuranosidase activity in A. japonicus (Duan et al, 1993) and F. oxysporum (Nishizawa et al, 1980). Metal ions can change the overall charge of proteins, thereby affecting their properties.…”
Section: Compoundsmentioning
confidence: 99%
“…Determination of FTase activity. Fructosyltransferase activity in culture filtrate was measured by estimating the liberated reducing sugar released from sucrose as described by Duan et al (1993) using glucose as a standard. The assay mixture contained appropriately 0.1 mL of the enzyme solution, (0.15 M Mcllvaine buffer pH 5.5) and 0.4 mL of 50% (W/V) sucrose solution.…”
Section: Methodsmentioning
confidence: 99%